How school climate influences bullying behavior tendencies in junior high school - Ramadhani, Aisyah Putri; Utami, Adnani Budi; Ul Haque, Sayidah Aulia (Institute of Computer Science (IOCS), 2025)
This study examines the design of an Islamic Religious Education (PAI) curriculum that promotes religious moderation in the digital era through a comprehensive literature review. The research aims to explore theoretical foundations, principles, and practical approaches for integrating religious moderation values into the PAI curriculum while addressing the challenges and opportunities presented by technological advancements. Using a qualitative approach, the study relies on primary and secondary literature, including academic books, journal articles, policy documents, and relevant educational research. Data were collected through systematic searches in academic databases using keywords such as